Nucleate pool boiling heat transfer on a titania nanotube-coated surface - Fan, Simiao (2020)
Enhancing nucleate boiling using surface modification techniques has become to a major topic of interest in pool boiling studies. In this paper, experiments are conducted on a vertically oriented copper surface and a titanium surface coated with TiO2 nanotubes. The nanotube coating is fabricated by a specific anodization process using ethylene glycol as the anodizing solution. A highly wetting dielectric coolant, Novec 7100, is used as the working fluid. A copper block heated by ceramic heater is used to simulate the high power density electronic. The nanotube coated surface shows a significant CHF (critical heat flux) enhancement up to 54% when compared to the plain copper. Various empirical correlations are applied to predict the experimental data. Among all the empirical correlations, the Rosehnow correlation and the Kutateladge correlation give good agreement with the measured data from the plain copper surface.